THE POTENTIAL OF APPLYING DESIGN THINKING TECHNOLOGY IN THE INTEGRATION OF HIGHER EDUCATION DISCIPLINES FOR DEVELOPING PHILOLOGY STUDENTS’ CREATIVE WRITING COMPETENCE (SCIENCE TIME JOURNAL, 2026)
This article explores the potential of Design Thinking as an innovative pedagogical approach for developing creative writing competence among philology students through the integration of higher education disciplines. Creative writing competence is conceptualized as a multidimensional construct that combines linguistic proficiency, textual coherence, stylistic flexibility, cultural awareness, and communicative effectiveness. The study aims to clarify the theoretical foundations of Design Thinking in language education, examine its alignment with interdisciplinary learning principles, and identify pedagogical implications for philological training. Through qualitative analysis of contemporary research in linguodidactics, writing pedagogy, and innovative teaching methodologies, the article demonstrates that Design Thinking fosters creativity, reflective learning, and collaborative engagement. The findings highlight the importance of process-oriented instruction and holistic assessment approaches that balance creativity with linguistic accuracy, thereby supporting the development of expressive and academically rigorous writing among philology students.